Risk factors of hemorrhagic transformation in acute ischaemic stroke: A systematic review and meta-analysis - Sun, Jiacheng; Lam, Christina; Christie, Lauren; Blair, Christopher; Li, Xingjuan; Werdiger, Freda; Yang, Qing; Bivard, Andrew; Lin, Longting; Parsons, Mark (Frontiers in Neurology, 2023)
Background Hemorrhagic transformation (HT) following reperfusion therapies for acute ischaemic stroke often predicts a poor prognosis. This systematic review and meta-analysis aims to identify risk factors for HT, and how these vary with hyperacute treatment [intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT)]. Methods Electronic databases PubMed and EMBASE were used to search relevant studies. Pooled odds ratio (OR) with 95% confidence interval (CI) were estimated. Results A total of 120 studies were included. Atrial fibrillation and NIHSS score were common predictors for any intracerebral hemorrhage (ICH) after reperfusion therapies (both IVT and EVT), while a hyperdense artery sign (OR = 2.605, 95% CI 1.212–5.599, I2 = 0.0%) and number of thrombectomy passes (OR = 1.151, 95% CI 1.041–1.272, I2 = 54.3%) were predictors of any ICH after IVT and EVT, respectively. Common predictors for symptomatic ICH (sICH) after reperfusion therapies were age and serum glucose level. Atrial fibrillation (OR = 3.867, 95% CI 1.970–7.591, I2 = 29.1%), NIHSS score (OR = 1.082, 95% CI 1.060–1.105, I2 = 54.5%) and onset-to-treatment time (OR = 1.003, 95% CI 1.001–1.005, I2 = 0.0%) were predictors of sICH after IVT. Alberta Stroke Program Early CT score (ASPECTS) (OR = 0.686, 95% CI 0.565–0.833, I2 =77.6%) and number of thrombectomy passes (OR = 1.374, 95% CI 1.012–1.866, I2 = 86.4%) were predictors of sICH after EVT. Conclusion Several predictors of ICH were identified, which varied by treatment type. Studies based on larger and multi-center data sets should be prioritized to confirm the results. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=268927, identifier: CRD42021268927.